2016
DOI: 10.4081/aiua.2016.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s satisfaction after 2-piece inflatable penile prosthesis implantation: An Italian multicentric study

Abstract: 2 pieces IPP appears to be associated with a low complication rate and good satisfaction of pts especially in the elderly. It also assures satisfactory rates of aesthetics and functional results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 12 publications
0
18
1
2
Order By: Relevance
“…Gentile et al found that patients older than 65 years were more satisfied with their two-piece prosthesis than younger patients [10]. In their series of 42 patients, all patients older than 65 were very or mostly satisfied with their implant compared with men younger than 65, of whom only 70% felt the same way.…”
Section: Discussionmentioning
confidence: 94%
“…Gentile et al found that patients older than 65 years were more satisfied with their two-piece prosthesis than younger patients [10]. In their series of 42 patients, all patients older than 65 were very or mostly satisfied with their implant compared with men younger than 65, of whom only 70% felt the same way.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent retrospective multicentric study, Gentile et al. reported their results in an analysis of a group of 42 patients who underwent a two‐piece IPP implantation from November 2005 to November 2013, in four centres with established experience. Every patient was asked to complete the Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) specifically modified, in order to assess their own satisfaction after surgery and, its impact on their quality of sexual life.…”
Section: Discussionmentioning
confidence: 99%
“…Ряду пациентов помогает медикаментозная терапия ингибиторами ФДЭ-5 как в таблетированной форме, так и в виде гелей для введения в уретру или внутрикавернозных инъекций [11,12]. При ее неэффективности используют хирургическое лечение -имплантацию протеза полового члена, что позволяет в подавляющем большинстве случаев восстановить половую функцию [13,14].…”
Section: обсуждение результатовunclassified
“…Соответственно, встает задача сексуальной реабилитации этих пациентов, что должно способствовать улучшению их психоэмоционального состояния. Медикаментозная терапия с помощью ингибиторов ФДЭ-5, хотя и оказывает определенное положительное действие у больных с нерезко выраженной ЭД [11,12], но у большинства больных требуется оперативное лечение -имплантация протеза полового члена различной конструкции, что позволяет в большинстве случаев добиться положительного результата [13,14].…”
unclassified